IL-17A, IL-22, IL-6, and IL-21 Serum Levels in Plaque-Type Psoriasis in Brazilian Patients - Priscilla Stela Santana de Oliveira; Pablo Ramon Gualberto Cardoso; Emerson Vasconcelos de Andrade Lima; Michelly Cristiny Pereira; Angela Luzia Branco Pinto Duarte; Ivan da Rocha Pitta; Moacyr Jesus Barreto de Melo Rêgo; Maira Galdino da Rocha Pitta (Mediators of Inflammation)
Psoriasis is a chronic inflammatory skin disease characterized by alterations in cytokines produced by both Th1 and Th17 pathways. The aim of this study was to evaluate serum levels of pivotal cytokines and correlate them with clinical parameters. Serum samples from 53 psoriasis patients and 35 healthy volunteers, matched by the proportion of sex and age ratios, were collected for ELISA cytokine detection. Psoriasis Area and Severity Index (PASI) was assessed at the time of sampling in psoriasis patients. Our findings demonstrate that IL-17A, IL-22, and IL-6 serum concentrations were significantly higher in psoriasis patients than in the control group. No statistical correlation could be found between cytokines concentrations, PASI score, and age in this study. Although our results do not show any correlation between serum levels of IL-17A, IL-22, and IL-6 and disease activity, the present study confirms that they were increased in Brazilian psoriasis patients in comparison to healthy volunteers.